Editorial. Letter of the Guest Editors to Readers - Gita Steiner-Khamsi; Elena Lenskaya (Вопросы образования, 2016)
Editorial to the special issue "Recruitment, Education and Retention of Teachers: Issues and Challenges in the Eastern/Central Europe, the Caucasus, Central Asia and Mongolia".